Cardiorespiratory and muscular endurance of sedentary children and adolescents with or without intellectual disability in the Democratic Republic of Congo - Teddy Bofosa; Betty Miangindula; Constant Nkiama; Eric Kam; Guy Bumoko (Turkish Journal of Kinesiology, 2019)
The aim of this study was to assess the level of physical fitness and sedentary children with disabilities included in Kinshasa. One hundred-thirty children were included in this study, 70 with intellectual disability (ID, age: 12.4 ± 4 years) and 60 without ID (age: 11.6 ± 4 years). Flexibility, explosive strength, grip strength, abdominal endurance, and cardiorespiratory endurance tests were used. They are supplemented by the measurement of anthropometric characteristics. Measurements of muscular strength endurance, isometric force, walking distance and cardiorespiratory endurance was significantly higher in comparison with ID (p<0.05). The muscular strength endurance, isometric strength walking distance and cardiorespiratory endurance of girls was significantly lower than those of the control group (p <0.05). It is clear from this study that the cardiorespiratory and muscular endurance of children and adolescents with intellectual disabilities is inferior to those of children without intellectual disabilities regardless of the type of children.